2004
DOI: 10.1096/fj.03-1263fje
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 functions intracellularly in human coronary artery endothelial cells: roles of LBP and sCD14 in mediating LPS‐responses

Abstract: Endothelial cells are activated by microbial agonists through Toll-like receptors (TLRs) to express inflammatory mediators; this is of significance in acute as well as chronic inflammatory states such as septic shock and atherosclerosis, respectively. We investigated mechanisms of lipopolysaccharide (LPS)-induced cell activation in human coronary artery endothelial cells (HCAEC) using a combination of FACS, confocal microscopy, RT-PCR, and functional assays. We found that TLR4, in contrast to TLR2, is not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 48 publications
12
105
0
3
Order By: Relevance
“…TLR4 was reported to reside and mediate LPS response intracellularly in epithelial and endothelial cells. [22][23][24] In human peripheral monocytes, TLR4 could be expressed either on cell surface or in the cytoplasm, and rapid recycling of TLR4-CD14-MD-2 complexes between the Golgi and plasma membrane could be observed. 25 These results suggested that both cell surface and intracellular TLR4 might contribute to cell response to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 was reported to reside and mediate LPS response intracellularly in epithelial and endothelial cells. [22][23][24] In human peripheral monocytes, TLR4 could be expressed either on cell surface or in the cytoplasm, and rapid recycling of TLR4-CD14-MD-2 complexes between the Golgi and plasma membrane could be observed. 25 These results suggested that both cell surface and intracellular TLR4 might contribute to cell response to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 expression has been demonstrated on various ECs and significantly increases under inflammatory conditions. TLR4 is expressed in coronary ECs (29) and is overexpressed and colocalizes with the p65 subunit of NF-B in coronary atherosclerotic plaques, suggesting activation of TLR4 at this site (21). This possibility is supported by the demonstration that LPS activates NF-B in dermal microvascular ECs and that LPS, IFN-␥, and TNF-␣ up-regulate TLR4 mRNA and protein (23).…”
Section: Innate Immunitymentioning
confidence: 92%
“…Studies using affinity chromatography, and later confirmed by fluorescence resonance energy transfer (FRET), revealed that LPS associates with the heat shock proteins, Hsp70 and Hsp90, chemokine receptor 4 (CXCR4) and growth differentiation factor 5 (GDF5). 49,50 In human coronary artery endothelial cells, TLR4 functions intracellularly, 51 suggesting that LPS uptake may be necessary for optimal signal transduction. Similarly, TLR4 colocalizes with LPS within the Golgi of intestinal epithelial cells 52 and functions within this intracellular compartment to recognize internalized LPS.…”
Section: Toll-like Receptor (Tlr)4 Signalingmentioning
confidence: 99%